SIFAT AMILOGRAFI PASTA PATI SUKUN TERMODIFIKASI MENGGUNAKAN SODIUM TRIPOLIFOSFAT - Medikasari, Medikasari; Nurdjanah, Siti; Yuliana, Neti; Lintang C S, Naomi (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2009)
Breadfruit (Artocarpus communis) could be used as food subtitute which currently is quite popular . Breadfruit is generally consumed as snack food in the form of boiled or fried chips. One effort to widen utilization of breadfruit as a source of food, it can be processed into natural starch as well as modified starch. The objective of this research was to observe the pasting properties of the modified breadfruit starch treated withd fifferent concentration of sodium tripolyphosphate The experiment consisted of four levels of STPP concentrations : control, 1%, 3% and 5% starch (db). All tsamples were replicated three times Keywords: breadfruit, sodium tripolyphosphate, pasting properties.